CHIEFS AS JUDGES IN MODERN GHANA: EXPLORING THE JUDICIAL ROLE AND CHALLENGES CONFRONTING THE ASHANTI REGIONAL HOUSE OF CHIEFS - Marfo, S. (UDS International Journal of Development, 2019)
Long before the advent of modern systems of governance and its adjudication arrangement of justice, the Ashantis of Ghana, like other African societies, had their own system of governance and conflict resolution mechanisms which revolved around the chieftaincy institution. However, with the advent of western-styled democracy and its modern court system, the chieftaincy institution of Ghana as in Ashanti, has been incorporated into the legal system of the country. With this development, the chief in modern day Ghana is perceived by many as basically a ceremonial figure who performs religious and cultural functions, with many even questioning the relevance of the whole traditional adjudication system. Against this background, the Ashanti Regional House of Chiefs was used in an explorative case study design to explore the role and the challenges confronting the chiefs in the resolution of conflicts. Using 33 traditional authorities selected purposely, data gathered through in-depth interview revealed that, chiefs as adjudicating members of the Judicial Committee still play an instrumental role in the resolution of chieftaincy conflicts bordering on nomination, selection, enstoolment, destoolment and misappropriation of stool property in the Ashanti Region. The study further revealed that the activities of the Regional House were fraught with challenges including: lack of training for chiefs on conflict resolution, absenteeism on the part of panel members and lawyers to litigants, and inadequate funding. These challenges as the study identified contributed to the delay in adjudication and piling up of chieftaincy cases. Keywords: Ashanti Regional House of Chiefs, Chief and Chieftaincy, Chieftaincy Conflict, Conflict Resolution, Judicial Committee.